Avrami exponent under transient and heterogeneous nucleation transformation conditions - Sinha I.; Mandal R.K. (My University, 2025)
The Kolmogorov-Johnson-Mehl-Avrami model for isothermal transformation kinetics is universal under specific assumptions. However, the experimental Avrami exponent deviates from the universal value. In this context, we study the effect of transient heterogeneous nucleation on the Avrami exponent for bulk materials and also for transformations leading to nanostructured materials. All transformations are assumed to be polymorphic. A discrete version of the KJMA model is modified for this purpose. Scaling relations for transformations under different conditions are reported. © 2010 Elsevier B.V. All rights reserved.